Factual Action As Administrative Disputes (Prohibition Of Misleading Lawsuit Between The Administrative Decision And The Factual Action) - Pasaribu, David (Universitas Islam kadiri, 2026)
This article attempts to comprehend the ideal concept of factual action and analyzes factual action as an object of dispute in the Administrative Court (